Synthesis of alpha-kainic acid from a 7-azabicyclo[2.2.1]heptadiene by tandem radical addition-homoallylic radical rearrangement. - Hodgson, D; Hachisu, S; Andrews, MD (2005)
Reductive radical addition of 2-iodoethanol to N-Boc 2-tosyl-7-azabicyclo[2.2.1]heptadiene gives N-Boc syn-7-(2-hydroxyethyl)-4-tosyl-2-azabicyclo[2.2.1]hept-5-ene, which is converted into the neuroexcitants 3-(carboxymethyl)pyrrolidine-2,4-dicarboxylic acid and alpha-kainic acid. [structure: see text]